In vivo human whole-brain Connectom diffusion MRI dataset at 760 µm isotropic resolution - Fuyixue Wang (Nature Portfolio, 2021)
Measurement(s) brain measurement Technology Type(s) magnetic resonance imaging Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14058443